ANALISIS KEUANGAN DAERAH UNTUK MENILAI EFEKTIVITAS DAN EFISIENSI PENGELOLAAN APBD DI KABUPATEN SIDOARJO - Deris Lilian Fisfia; Dwi Ayu Ijayanti; Eva Hany Fanida; Melda Fadiyah Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of effectiveness in realizing Regional Original Revenue (PAD) within the established targets, as well as assess the level of efficiency in budget utilization and identify the regional government's ability to manage financial resources. The research method used is descriptive quantitative, using the following formulas: Independence Ratio, Effectiveness Ratio, Efficiency Ratio, and Growth Ratio. The results reveal that the independence ratio averages 81.73%, categorized as delegative. The effectiveness ratio is above 100.00% annually, indicating that regional government performance is highly effective. The efficiency ratio tends to fluctuate, hovering around 100.00%, indicating that regional expenditure management is inefficient. Meanwhile, the growth ratio is on a positive trend, averaging 14.06%, indicating that regional governments have a significant capacity to increase regional revenue.